Engineering chiral mesoporous silica nanoparticles: Template design and structural control for advanced applications - Yu Yin; Wu Wei; Kai Zhang (Supramolecular Materials)
Chiral mesoporous silica nanoparticles (CMSNs) are a distinct subset of mesoporous silica nanoparticles, combining the favorable physicochemical properties of MSNs with unique chiral architectures at both molecular and macroscopic scales. These helical structures endow CMSNs with specialized functionalities, enabling their applications in chiral catalysis, enantioselective recognition, chiral separation, drug delivery, and optical devices, making them a focal point in materials and biomedical research. Significant progress has been achieved in the synthesis of CMSNs, particularly in understanding the mechanisms of chirality formation and the critical role of surfactant templates in guiding chiral structures. This review summarizes these advancements, emphasizing experimental and theoretical insights. Key applications of CMSNs, especially in drug delivery systems, are explored in detail, highlighting their potential to enhance bioavailability and therapeutic efficacy. Looking ahead, CMSN research presents exciting opportunities, including precise control over chiral structures, the development of novel templating strategies, and the exploration of broader applications. These advancements are expected to drive progress in nanoporous silica technologies and open new frontiers in materials science and nanomedicine.